Premodern rulership and contemporary political power : the king's body never dies - Mroziewicz, Karolina Anna, 1983-; Sroczyński, Aleksander (Central European medieval studies ;, 2017)
In the medieval period, the monarch was seen as the embodiment of the community of his kingdom, the body politic. And while we've long since shed that view, it nonetheless continues to influence our understanding of contemporary politics. This book offers thirteen case studies from premodern and contemporary Europe that demonstrate the process through which political corporations - bodies politic - were and continue to be constructed and challenged. Drawing on history, archaeology, literary criticism, and art history, the contributors survey a wide geographical and chronological spectrum to offer a panoramic view of these dynamic political entities.